(untitled) (Publicaciones en Ciencias y Tecnología, 2024)
Artificial intelligence (AI) has rapidly become a transformative force in every aspect of our lives. From the way we work and communicate to the way we make decisions and solve problems, AI is changing the world around us. However, one of the controversies surrounding its application is its impact on the planet’s sustainable development. In this editorial, we briefly discuss what can be done to balance its application with environmental protection and social well-being.